A Simple and Efficient In Vivo Non-viral RNA Transfection Method for Labeling the Whole Axonal Tree of Individual Adult Long-Range Projection Neurons - Porrero, César; Rodríguez-Moreno, Javier; Quetglas, José I.; Smerdou, Cristian; Furuta, Takahiro; Clascá, Francisco (Frontiers in Neuroanatomy, 2016)
We report a highly efficient, simple, and non-infective method for labeling individual long-range projection neurons (LRPNs) in a specific location with enough sparseness and intensity to allow complete and unambiguous reconstructions of their entire axonal tree. The method is based on the “in vivo” transfection of a large RNA construct that drives the massive expression of green fluorescent protein. The method combines two components: injection of a small volume of a hyperosmolar NaCl solution containing the Pal-eGFP-Sindbis RNA construct (Furuta et al., 2001), followed by the application of high-frequency electric current pulses through the micropipette tip. We show that, although each component alone increases transfection efficacy, compared to simple volume injections of standard RNA solution, the highest efficacy (85.7%) is achieved by the combination of both components. In contrast with the infective viral Sindbis vector, RNA transfection occurs exclusively at the position of the injection micropipette tip. This method simplifies consistently labeling one or a few isolated neurons per brain, a strategy that allows unambiguously resolving and quantifying the brain-wide and often multi-branched monosynaptic circuits created by LRPNs.